Adobe Flash-Based Interactive Media Development on Social Studies Learning Outcomes Class IV - Lestari, Rizky Mega; Estiastuti, Arini (Elementary School Teacher, 2021)
This study was motivated by the use of technology-based learning media that was not optimal, thus resulting in low socialstudies learning outcomes. This study aims to develop interactive learning media based on Adobe Flash with the NHTmodel on social studies learning outcomes. This study used a quantitative approach with the type of research anddevelopment (RD). The subjects of this study were 20 students in grade IV at SDN Bumiharjo 2 Demak. Observations,Interviews, questionnaires, tests, and documentation were carried out to collect the data. Data analysis was conducted bya feasibility test and media effectiveness test. The results showed that Adobe Flash-based interactive media is feasible tobe used with the assessment of media experts and material experts obtained percentages of 100% and 96.8%. This mediais effectively used based on the results of the t-test showed tcount (5.690) ttable (2.024), then Ha is accepted, while theaverage increase (n-gain) from the initial test to the final test was 0.60 with moderate criteria. The conclusion of this studyis that Adobe Flash-based interactive learning media with the NHT model is feasible and effective to use in social studieslearning for class IV.Keywords: Adobe Flash-based interactive media, learning outcomes. social studies